Phase Change Materials in Electrothermal Conversion Systems: A Review - Rafał Twaróg; Piotr Szatkowski; Kinga Pielichowska (Energies)
Green energy harvesting is one of the most important and evolving research areas. Solar energy is an inexhaustible and environmentally friendly energy source, and phase change materials (PCMs) are capable of improving photovoltaic devices by heat storage and could have a positive impact on sustainable energy utilization. This review presents the current state of the art on PCMs and their modifications for electrothermal energy conversion applications. The paper focuses on PCMs characteristics and their properties required for electrothermal energy conversion systems, and it presents various methods of PCMs modification intended to obtain multifunctional systems based on these materials as well as electrothermal conversion and energy storage mechanisms and selected applications. The goal of this review is to present different types of PCM modifications to obtain multifunctional PCM-based systems for electrothermal energy conversion.